2019
DOI: 10.1007/s12519-019-00286-8
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an efficient reverse genetic system of Mumps virus S79 from cloned DNA

Abstract: BackgroundMumps is a common type of respiratory infectious disease caused by mumps virus (MuV), and can be effectively prevented by vaccination. In this study, a reverse genetic system of MuV that can facilitate the rational design of safer, more efficient mumps vaccine candidates is established.MethodsMuV-S79 cDNA clone was assembled into a full-length plasmid by means of the GeneArt™ High-Order Genetic Assembly System, and was rescued via reverse genetic technology. RT-PCR, sequencing, and immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Recently, cotton rats have been regarded as improved small animal model for human paramyxoviruses and pneumoviruses including studying viral infection and pathogenesis, testing vaccine efficacy and evaluating antiviral drugs (Boukhvalova and Blanco 2013;Green et al 2013). In our previous research, we found viruses can be detected in the lung of the cotton rat after mumps infection as in IFN-a/b R -/mice (Zhou et al 2019b). In this study, we found that neither the parental rMuV-S79 nor wild type MuV strains caused significant histologic lesions in the lungs of unvaccinated cotton rats.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, cotton rats have been regarded as improved small animal model for human paramyxoviruses and pneumoviruses including studying viral infection and pathogenesis, testing vaccine efficacy and evaluating antiviral drugs (Boukhvalova and Blanco 2013;Green et al 2013). In our previous research, we found viruses can be detected in the lung of the cotton rat after mumps infection as in IFN-a/b R -/mice (Zhou et al 2019b). In this study, we found that neither the parental rMuV-S79 nor wild type MuV strains caused significant histologic lesions in the lungs of unvaccinated cotton rats.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we used BHK cells stably expressing T7 RNA polymerase to rescue rMuVs, which prevents the risk of being contaminated by vaccinia virus. This method has been approved in other studies for rescue of human metapneumovirus, bovine respiratory syncytial virus and measles virus (Ma et al 2014;Sun et al 2014;Zhang et al 2014;Cui et al 2017;Pang et al 2018;Wang et al 2018;Zhou et al 2019b). We have effectively rescued rMuV-S79 without helper vaccinia virus in our previous researches (Zhou et al 2019a(Zhou et al , 2019b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A DNA vaccination platform was used to design a full-length complementary DNA (cDNA) clone of recombinant MuV-S79 mumps virus by reverse genetics ( Zhou et al, 2019 ). The cDNA clone was administered intranasally to cotton rats to test its efficacy as a potential vaccine.…”
Section: Future Prospects For Mumps Vaccinesmentioning
confidence: 99%
“…The experimental vaccine elicited an efficient, long-lasting neutralizing antibody immune response, as evidenced by sera obtained and tested 4 weeks after immunization. The vaccine induced complete protection against challenge with a wild-type mumps strain ( Zhou et al, 2019 ).…”
Section: Future Prospects For Mumps Vaccinesmentioning
confidence: 99%